The Influence Of The Leadership And Character Of A Pastor On The Spiritual Growth Of The Congregation At The GPdI Alfa Omega Church. - Setya Hari Purnomo; Daniel Ari Wibowo (Sekolah Tinggi Teologi Injili Indonesia Surabaya, 2021)
Leadership is a task given by Jesus Christ to Christians through His Church. Leaders are needed by every human being to achieve happiness and prosperity in all fields. Thus the Church has an important role in improving leadership for the spiritual growth of God's congregation because through qualified leaders people can understand correctly how to actually follow God. With this quality leader, people can understand who and for what God created them. Seeing the existence of a congregation that always needs guidance in spiritual growth, and that requires someone who can accompany The congregation is a leader or shepherd who is often referred to as the Pastor of the congregation. And not many Christian ministers or often referred to as Congregational Pastors have these criteria. So that they cannot be an example in the lives of the people they lead. So there are criteria set out in the Bible to become a Christian leader with quality and character. A leader is someone who deserves to be a role model for others because the leader has good character and becomes a leader blessing for the church he leads.